Use of alternative biofertilizers in the cultivation of forage cactus: A review (Research, Society and Development, 2021)
The forage cactus (Opuntia and Nopalea) is one of the most important forages in the world, native to Mexico, belonging to the Cactaceae family, and has high water-use efficiency. In Brazil, it is grown mainly in the Northeast, where it is considered strategic due to the climatic conditions of the region. Research indicates that organic fertilization induces a better productive performance of the forage cactus. In this sense, the use of biofertilizer to supply the nutritional needs of agricultural crops has been an important tool for rural producers, as it is a low-cost organic input, resulting from the aerobic fermentation of organic matter and water, and which can positively influence the chemical and physical properties of the soil. This literature review aims to present alternatives of agricultural practices with organic fertilization such as the use of biofertilizers in cultivation systems with forage cactus aiming at promising alternatives with efficient cultivation. It is concluded that the cultivation of forage cactus with the use of alternative organic biofertilizers, increases the production of plants, and enables low-cost techniques to rural producers.